Plasma-catalytic system with wide-aperture rotating gliding discharge - Nedybaliuk, O.A.; Fedirchyk, I.I.; Chernyak, V.Ya. (Вопросы атомной науки и техники, 2019)
This paper presents the results of the study of the wide-aperture rotating gliding discharge which was used for the plasma-catalytic reforming of hydrocarbons into synthesis gas. The photographs were compared with the oscillograms that represented the voltage of the wide-aperture rotating gliding discharge. The emission spectra of the plasma torch of the wide-aperture rotating gliding discharge were investigated for cases of when the reaction chamber was supplied with air and ethanol-air mixture. The distributions of electron Te, vibrational Tv and rotational Tr temperatures alongside the plasma torch inside the reaction chamber were determined.